Ω-Assisted α nucleation in a metastable β titanium alloy. (October 2019) - Shi, Rongpei; Zheng, Yufeng; Banerjee, Rajarshi; Fraser, Hamish L.; Wang, Yunzhi
Abstract: We investigate mechanisms of ω-assisted α nucleation for microstructure refinement in a metastable β titanium alloy, Ti-20V (wt%). In particular, we analyze quantitatively the individual and combined effects of concentration and stress fields associated with a growing isothermal ω precipitate and the potency of the ω/β interface on the activation energy barrier for α nucleation as a function of the ω precipitate size and coherency state. We find that the complex interplay among these three factors determines the most potent ω particle size for inducing α nucleation and the most favorable nucleation site. Graphical abstract: Unlabelled Image